Factors Associated With Medication Compliance in Elderly Patients With Type 2 Diabetes Mellitus: A Cross-Sectional Study - Wakui, Nobuyuki; Ozawa, Mizue; Yanagiya, Takahiro; Endo, Saki; Togawa, Chikako; Matsuoka, Raini; Shirozu, Shunsuke; Machida, Yoshiaki; Kikuchi, Mayumi (Frontiers in Public Health, 2022)
The average age of patients with type 2 diabetes in Japan is over 70 years. Elderly patients tend to have poor medication compliance, therefore, it is important to understand their individual situations to improve medication compliance, the treatment of their diabetes, and their quality of life (QOL). This study aimed to identify factors associated with medication compliance in elderly type 2 diabetic patients. A cross-sectional study based on questionnaires was conducted on type 2 diabetes patients aged 65 years or older. The participants were recruited from patients who visited three dispensing pharmacies in the Shinagawa area of Tokyo between March 1 and September 30, 2019. The questionnaire consisted of patient information (sex, age, medication compliance status, knowledge of drug effects and side effects), 12-Item Short Form Survey quality of life rating scale (SF-12), and Diabetes Treatment Satisfaction Questionnaire (DTSQ). Factors related to medication compliance were then evaluated. In all, there were 47 respondents: 31 males and 16 females. Four factors were found to be associated with medication compliance in elderly type 2 diabetic patients: medication storage (P = 0.01), knowledge of drug effects (P < 0.001), knowledge of side effects (P = 0.026), and physical functioning: (PF) (P = 0.045), a subscale of SF-12. Furthermore, the strength of the association between these four factors and medication compliance was calculated using Cramer’s coefficient of association. Knowledge of drug effects was the most strongly associated (knowledge of drug effects: V = 0.559; knowledge of side effects: V = 0.464; medication storage: V = 0.451; PF: V = 0.334). Because diabetes mellitus has no subjective symptoms and treatment effects are not felt to a great extent, it is difficult to motivate patients to consistently adhere to medication. When pharmacists provide medication guidance to elderly patients with type 2 diabetes mellitus, it is important to provide sufficient information to ensure they fully understand the drug effects to maintain medication compliance.